Pengaruh Relaksasi Otot Progresif terhadap Penurunan Dismenore pada Mahasiswi A 2012 Fakultas Keperawatan Unand : The Effect of Progressive Muscle Relaxation on Decreasing Dysmenorrhea in Student A 2012 Faculty of Nursing Unand - Israd Akbar; Dewi Eka Putri; Esi Afriyanti (Fakultas Keperawatan Universitas Andalas, 2014)
Dysmenorrhea is menstrual pain that is felt when, mainly in the lower abdomen to the waist andthighs spread that feels like cramping. The pain is subjective. In the severe circumstances can be accompaniedby nausea and vomiting. 60-70% of patients with dysmenorrhea are younger women, resulting in a sense ofdiscomfort and disruption have an impact on daily activities, academic and social. One of the nonpharmacological therapies that can be used to reduce dysmenorrhoea is progressive muscle relaxation. Thisstudy aims to determine whether the effect of progressive muscle relaxation in the pain management ofdysmenorrhoea. Subject is a student at A 2012 study in the Faculty of Nursing Andalas. This research uses aquasi-experimental approach with no control group with one group pretest-posttest. Sampling using samplingwith 37 people. Data analysis using the Wilcoxon. The research proves there is significant before and afterprogressive muscle relaxation to pain dysmenorrhoea on student A 2012 Faculty of Nursing in AndalasUniversity with p = 0.000 (p <0,05). This shows that progressive muscle relaxation can reduce the pain ofdysmenorrhoea on student A 2012 Faculty of Nursing in Andalas University. This shows that progressivemuscle relaxation can reduce the pain of dysmenorrhoea A 2012 School of Nursing student Andalas. It isrecommended for young women in order to implement progressive muscle relaxation in overcomingdysmenorrhoea.